"It Will Never Happen to Me!" - Black, Claudia (New York : Ballantine Books, 1987)
Examines the experiences and feelings of people raised in alcoholic homes, and offers guidelines that can positively affect children of alcoholics as they continue into adulthood.
Cover has subtitle: Children of alcoholics as youngsters, adolescents, adults.
Keywords: Children of alcoholics; Alcoholism; Alcoholics -- Family relationships; Alcoholism; Family